"We keep adding new problems" – an Interview with John Hartwig. Issue 2 (31st January 2023) - Zbikowski, Frauke
Abstract: John Hartwig is co‐discoverer of the Buchwald‐Hartwig amination – a widely used palladium‐catalyzed coupling reaction for the formation of C‐N bonds. For his research, he received the Emanuel Merck Lectureship last year. A discussion about creativity, useful reactions and pricey metals.